Participatory Research and Gender Analysis: Annual Reports and Medium Term Plans: 1997 through 2011 - CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation (1997)
Annual reports and Medium term plans of the CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation from 1997 though 2011.